On the Formation of Critical Thinking of Students of a Higher Educational Institution - Yessekeshova, Maral D.; Ibrayeva, Kulyan Zh.; Kaltayeva, Gulnar K.; Albytova, Nazymgul; Bekbayeva, Zhanar S. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The paper examined for the first time the features of the formation of systemic critical thinking of students of a higher educational institution, using systemic methods specially developed for this. Background: Unfortunately, there is practically no specific technology or even a method that specifically solves the problem of forming critical thinking. Nevertheless, each person who did not even receive the skills of critical thinking in the learning process possesses this type of thinking to some extent. Method: The method of systemic structuring and studying information about the objects in question solves important tasks of developing ways of thinking that are very relevant for future specialists. Implementing the methods of systemic cognition of the studied objects and the surrounding reality ensured the development of the systematic knowledge, skills, and systemic and other relevant ways of thinking and a systematic approach in cognitive and other activities. Results: The peculiarity of what has been said is that students in the process of implementing this method learn and develop simultaneously the proposed types of activities (actions) and the corresponding ways of thinking, including critical ones, determined by them. The particularly important result of the implementation of a systematic approach and systematic methods developed on its basis is the formation of systematic-critical thinking. Conclusion: The concept of systematic-critical thinking has been developed. Using a systematic approach as a scientific method allowed to significantly transform not only theory and practice but also existing traditional technologies of the formation of critical thinking.